Insect bite hypersensitivity in horses - Rosanna Marsella; Nicky Craig; Carissa Wickens; Samantha Brooks (EDIS)
Allergic skin disease is a very common cause of itching in horses. The itching can severely affect the horse?s quality of life, leading to the horse wounding itself by biting or scratching, and it can reduce the utility of the horse. This 4-page fact sheet written by Rosanna Marsella, Nicky Craig, Carissa Wickens, and Samantha Brooks and published by the UF/IFAS Department of Animal Sciences explains how to manage allergic skin disease, control itching, treat secondary infections, and prevent the insect bites in the first place. https://edis.ifas.ufl.edu/an359